PERANCANGAN GORONTALO CONVENTION AND EXHIBITION CENTER DENGAN PENDEKATAN ARSITEKTUR REGIONALISME - Safii, Zulfikar; Adam, Fikry; Djau, Bambang (Universitas Bina Taruna Gorontalo, 2025)
This study aims to design a Convention and Exhibition Center in Gorontalo using a regionalist architectural approach that blends local cultural identity with modern technology. This approach is intended to create a multifunctional space that not only facilitates meetings and exhibitions but also becomes an architectural landmark that responds to local climate and sociocultural needs. Through spatial needs analysis, comparative studies, and the application of regionalist design principles, the proposed design integrates meeting, exhibition, and recreational functions in a unified architectural form. The Gorontalo Convention and Exhibition Center is expected to increase tourist visits, strengthen cultural identity, and drive sustainable local economic growth.